Evaluación del impacto operativo y financiero del incumplimiento de las obligaciones tributarias de la contribuyente Paquita Vallejo - Siguenza Barzallo, Candy Giomara (2015)
The present research has as main objective to evaluate the operational and financial impact of noncompliance with tax obligations, through a management model or work report which will give taxpayers and this sector is the main source of other income monitoring the activities of its subsidiaries to incur no current legal regulations. As the authors point out Carlos Marco & David governments develop their fellow citizens and work together for the same need for a strong financial resource that not only come from loans or as in our case oil, bananas, cocoa and others; also strongly influenced by tax countries. For the preparation of this research work has been carried out in the form of documentary research, which has been based on articles indexed journals and others. It has also used the interview and observation methodology, as well as the technique of data collection, being a key support for the development of work; which it is why we recommend that the paper work is stipulated along with the internal policies of the company, in order to comply 100% with the provisions therein.